2014
DOI: 10.1155/2014/709217
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence on the Impact of Antithrombotics in Patients Submitted to Small Bowel Capsule Endoscopy for the Evaluation of Obscure Gastrointestinal Bleeding

Abstract: Objectives. Small bowel capsule endoscopy (SBCE) plays a decisive role in the obscure gastrointestinal bleeding (OGIB) diagnosis. Antithrombotics may increase bleeding risk in patients with preexistent lesions or through direct mucosal aggression. We aimed to correlate antithrombotics usage with lesions with bleeding potential found in SBCE. Methods. Retrospective single-center study including 274 consecutive SBCE performed over 7 years for OGIB. The lesions were classified as P0 (no bleeding potential), P1 (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…P2 lesions are known to have a high bleeding potential, with some studies reporting a rebleeding rate of up to 36.8%[ 16 ]. Different studies have also reported several factors that are associated with P2 lesions on SBCE of patients with IDA, namely NSAID and antiplatelet use, higher transfusion requirements, moderate to severe chronic kidney disease, older age, hypertension, hypercholesterolemia, and anticoagulants[ 6 , 7 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…P2 lesions are known to have a high bleeding potential, with some studies reporting a rebleeding rate of up to 36.8%[ 16 ]. Different studies have also reported several factors that are associated with P2 lesions on SBCE of patients with IDA, namely NSAID and antiplatelet use, higher transfusion requirements, moderate to severe chronic kidney disease, older age, hypertension, hypercholesterolemia, and anticoagulants[ 6 , 7 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“… 53 Independent risk factors associated with an increased diagnostic yield of SBCE in OGIB include the presence of overt OGIB, 56 shorter interval between presentation and the procedure, 57 recurrent OGIB with >6 months of duration or more than one bleeding episode, 21 advanced age 50 and antithrombotic use. 58 The diagnostic yield may be further improved by the use of chromoendoscopy techniques, such as the Flexible Spectral Imaging Colour Enhancement (FICE, Fujinon Corporation ® , Saitama, Japan), incorporated in Given Imaging ® (Yoqneam, Israel) software, that enhance surface patterns to better observe mucosal lesions, 59 , 60 , 61 and the use of such techniques should be considered in patients where a strong suspicion for small bowel abnormalities remain despite a negative SBCE.…”
Section: Obscure Gastrointestinal Bleedingmentioning
confidence: 99%
“…Use of antithrombotics including antiplatelet agents and anticoagulants is associated with upper and lower GI bleeding. ( 8 10 ) Recent studies revealed that users of antithrombotics constitute a large proportion of OGIB patients who require examination of the small intestine using an SBCE, ( 5 , 11 ) and OGIB patients using antiplatelet agents and anticoagulants are more likely to show positive findings on SBCE examination than those not administered such agents. ( 11 , 12 )…”
Section: Introductionmentioning
confidence: 99%